The Present Of Diglossia In Social Media - Nasiroh Khoirun Nisa, Luthfi; Rohma Khurniawati, Desi; Setyowati, Ratini (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Recently, Indonesian people often use non-standard Indonesian language. This is due to the fusion of languages that occurs as a result of globalization. Social media is also not spared from this phenomenon, especially the Twitter application. This study will discuss the use of the Diglossia language variety used by the Indonesian people on Twitter social media. For data collection, the author uses a qualitative descriptive method to analyze the data. The theory focuses on grammar and language function. The results of this study indicate that the language used by the Indonesian people on Twitter is divided into two variations of language, namely formal and informal. Most of the websites of government, health issues, politics, and education use a variety of formal language in each of their posts. While the general public who do not spread the above issues from teenagers to adults use a variety of informal languages. This proves that in every use of Indonesian, Indonesian people still have a variety of languages called Diglossia, even in social media applications.